Hydrodynamic Forces and Wake Distribution of Various Ship Shapes Calculated Using a Reynolds Stress Model - Satoshi Matsuda; Tokihiro Katsui (Journal of Marine Science and Engineering, 2022)
The Reynolds-averaged Navier–Stokes (RANS)-based computational fluid dynamics (CFD) calculation using a two-equation turbulence model, such as the k–omega shear-stress transport (SST) model, is a mainstream method with sufficient accuracy for the estimation of integral hydrodynamic forces and moment at both the model-scale and full scale. This paper confirmed that the Reynolds stress model (RSM) has sufficient estimation accuracy of viscous resistance and wake distribution at the hull design stage. Herein, the ability of RSMs to estimate the viscous resistance and wake distribution of a JBC ship is evaluated. Specifically, the verification and validation (V&V) method is employed to indicate the numerical and model uncertainties of each turbulence model used to estimate the viscous resistance. The RSMs showed higher numerical uncertainty than the k–omega SST. However, the uncertainty of the experimental measurements is generally smaller than the numerical uncertainty. Moreover, the linear pressure–strain (LPS) and the linear pressure–strain two-layer (LPST) models show less comparison error of the viscous resistance than the k–omega SST. Furthermore, the LPST and k–omega SST models are applied to twenty ships with various full and fine hull forms to calculate the viscous resistance and compare it with the experimental results. The viscous resistance of the LPST model showed a small difference when employed in experimental fluid dynamics (EFD) and CFD calculations. Using the LPST model, the viscous resistance can be estimated with high accuracy in our setting. For industrial use, this study could provide an important insight into the designing of various types of vessels.